Search 74,313 tutors
FIND TUTORS
Ask a question
0 0

How do you simplify this?

Tutors, please sign in to answer this question.

2 Answers

Assuming the original problem is: [(m/4)*(n/3)]-1 divided by [(-5m/-3)*(n4)]2

The numerator becomes  (mn/12)-1. Any fraction to the -1 power is just flipped, so this becomes 12/mn

The denominator becomes (-5mn4/-3)2  Squaring a fraction means squaring its numerator and denominator, so this becomes 25m2n8/9.

Put them together you get  (12/mn)/(25m2n8/9) = (12/mn) * (9/25m2n8

                                          Multiply across:      = 108/25m3n9

Assuming the original problem is:  [(m/4)*(n/3)]-1 divided by [(-5m/-3)*(n4)]2

 

= 1 divided by [(mn/12)] [(5mn4/-3)2]

= 1 divided by (mn/12) (25m2n8/9) = 1 / (25m3n9/108) = 108 / 25m3n9